PENGARUH PROFITABILITAS TERHADAP PREDIKSI KEBANGKRUTAN DENGAN STUKTUR MODAL SEBAGAI VARIBEL MODERATING - Khusnul Khotimah; Indah Yuliana (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2020)
This study aimshfor the purpose of this study which ismto determine the effect of profitability on bankruptcy predictions. Working Capital Moderation is rarely done by other studies. And find out whether the company in the cement industry has the potential to go bankrupt. The sample used in this study was 4 companies incorporated in the Cement Sub Sector which were incorporated on the IDX (IndonesiapStock Exchange). The analytical methodoused is a descriptive statistical method with thepModerated Regretion Analyze analysis tool. Thepresults of this studypindicate that there is a significant negative effect of the ROA variable on bankruptcy predictions. The DER variable is able to moderate the relationship between ROA and bankruptcy. By using the Atlman Z-Score model it can be seen that from the five study samples there were 3 companies that were classified as healthy, one company classified as gray, and one company that was potentially bankrupt.